Implementasi aplikasi “Mentari” assessment berbasis kearifan lokal Sunda pada remaja untuk peningkatan literasi dan ketahanan mental - Hertini, Reni; Rohita, Tita; Wahyudin, Asep; Riyantina, Ade Sity; Cahyani, Gita; Berliani, Melin; Awaliyah, Rida Nurfarida; Mubarok, Resdyana (Holistik Jurnal Kesehatan, 2026)
Background: Adolescent mental health is a critical issue currently of global, national, and local concern. According to data from the World Health Organization (WHO), more than 970 million people worldwide experience mental disorders, with depression and anxiety disorders being the two most common conditions. Specifically, the WHO states that approximately 1 in 7 adolescents aged 10–19 years experience a mental disorder. Purpose: To analyze the implementation of the "Mentari" assessment app, based on Sundanese local wisdom, for adolescents to improve mental literacy and resilience. Method: A quantitative approach with a single-group pre-posttest (single-group pretest–posttest) quasi-experimental design was used. Participants were 117 adolescents in Ciamis Regency. The sample was selected using a non-probability purposive sampling technique. Data were analyzed using the Wilcoxon Signed Rank Test. Results: There was a significant difference between anxiety and depression levels before and after using the "Mentari" assessment app, with a downward trend. Conclusion: The "Mentari" app intervention was shown to have a significant impact on reducing participants' anxiety and depression levels. The integration of a digital approach with the cultural values ​​of silih asah, silih asih, and silih asuh makes this application effective as a medium for early detection and support for promotive-preventive mental health efforts.   Keywords: Adolescents; Digital-Based Intervention; Mental Health Literacy; Mental Resilience; Sundanese Local Wisdom.   Pendahuluan: Kesehatan mental remaja merupakan isu penting yang saat ini menjadi perhatian global, nasional, maupun lokal. Berdasarkan data dari World Health Organization (WHO), lebih dari 970 juta orang di seluruh dunia mengalami gangguan mental, dengan depresi dan gangguan kecemasan sebagai dua kondisi yang paling umum. Secara khusus, WHO menyebutkan bahwa sekitar 1 dari 7 remaja usia 10–19 tahun mengalami gangguan mental. Tujuan: Untuk menganalisis Implementasi aplikasi “Mentari” assessment berbasis kearifan lokal Sunda pada remaja untuk peningkatan literasi dan ketahanan mental. Metode: Pendekatan kuantitatif dengan desain quasi-experimental pre-post single group (one-group pretest–posttest). Partisipan adalah remaja di Kabupaten Ciamis sebanyak 117 siswa. Pemilihan sampel dilakukan secara non-probabilitas purposive. Data dianalisis menggunakan uji Wilcoxon Signed Rank Test. Hasil: Terdapat perbedaan yang bermakna antara tingkat kecemasan dan depresi sebelum dan sesudah penggunaan aplikasi “Mentari”  Assessment dengan arah perubahan yang cenderung menurun. Simpulan: Intervensi aplikasi “Mentari” terbukti memberikan pengaruh yang signifikan terhadap penurunan tingkat kecemasan dan depresi partisipan. Integrasi pendekatan digital dengan nilai budaya silih asah, silih asih, dan silih asuh menjadikan aplikasi tersebut efektif sebagai media deteksi dini dan pendukung upaya promotif-preventif kesehatan mental.   Kata Kunci: Intervensi Berbasis Digital; Kearifan Lokal Sunda; Ketahanan Mental; Literasi Kesehatan Mental; Remaja.